Bliskowschodnia polityka energetyczna Chin - Obeidat, Hayssam (The Middle East energy policy of China, 2009)
The strategical value of the Middle East as well as this stemming out from its natural resources has made it become an area of conflicting interests among the superpowers and a trouble spot of their competition. This paper treats the issue of Chinese expansion in the Middle East. It also contains an attempt to analyze the problem of strong competition between the USA and China over the control of oil in the Middle East. The total reliance of Chinese economy on foreign supplies of natural resources and the control of the USA in the Middle East has initiated the new oil policy of China searching for new allies. There have been significant investments made not only in the Middle East but also in Africa, Latin America and former Soviet Union countries. The great increase in importance of Iran and its cooperation with China generates accusations from the American side, that China has the intentions of controlling the energy resources in different parts of the world. These accusations are also related to Chinese alliance with oil countries alleged to support the terrorism. China is now facing the conflict with American interests, and it has to find the golden mean in balancing its relations with Iran and the United States
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67